Processing Theory in Islamic Thought: A Comparative Analysis of Al-Mawardi and Ibn Khaldun with Implications for Islamic Education - Asysyauqi, Muhammad Farid (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2025)
Al-Mawardi and Ibn Khaldun devoted many thoughts to education. Both of them also described most aspects of language, transfer, memory, recalling, and moreover retrieval of information which is important in information processing theory. The purpose of this research is to describe and analyze the learning concepts of Al-Mawardi and Ibn Khaldun according to processing theory as a framework of analysis. The method used is library research which examines many of their works and most works which describe them as primary and secondary sources. The analysis technique uses the OMA system (Optimal Matching Analysis). The results of this research show that Al-Mawardi postulated many linguistic aspects and effective strategies for conveying information either orally or in writing. He tends toward depth level processing in which metacognitive aspects, self-regulation, and understanding of introductory language become the core keys. On the contrary, Ibn Khaldun appears to compare between two levels of processing, either depth or storage level. His unique thought differs from contemporary brain structure in which Ibn Khaldun describes that sensory becomes the foremost gate of information which will be input to the back brain with a certain operational system processed from front to back brain. Either Al-Mawardi or Ibn Khaldun have no far difference, but their similarity is that the urgency of linguistic understanding becomes an essential window for a person to recognize until they know. The conclusion is that they are the same in postulating depth level, but Ibn Khaldun not only focuses on that but also gives a theoretical concept of storing information integrally from front to foremost brain.